2019
DOI: 10.1590/0034-7167-2018-0800
|View full text |Cite
|
Sign up to set email alerts
|

Time series of hospitalizations of adolescents due to mental and behavioral disorders

Abstract: Objective: to analyze the trend of hospitalizations of adolescents due to mental and behavioral disorders in Paraná, from 1998 to 2015. Method: ecological study of time series. Data were analyzed by means of segmented linear regression modeling for time series, estimated for each of the four health macro-regions. Results: the East macro-region showed a greater trend to increase hospitalizations from January 1998 to November 2003 (β1=0.006, p<0.001). In other macro-regions, there were similar trends with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“… 18 In addition, a time series analysis conducted in Paraná revealed that the main cause of hospitalizations in adolescents was mental and behavioral disorders caused by the use of psychoactive substances, accounting for 64.35% of hospitalizations in this age group between 2012 and 2015. 10 One possible explanation for this phenomenon is that the perception of psychoactive substances use differs according to region. According to a study on adolescent alcohol-related behaviors, the Northern region of the country is associated with more reports of fear and insecurity regarding chemical dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 In addition, a time series analysis conducted in Paraná revealed that the main cause of hospitalizations in adolescents was mental and behavioral disorders caused by the use of psychoactive substances, accounting for 64.35% of hospitalizations in this age group between 2012 and 2015. 10 One possible explanation for this phenomenon is that the perception of psychoactive substances use differs according to region. According to a study on adolescent alcohol-related behaviors, the Northern region of the country is associated with more reports of fear and insecurity regarding chemical dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The use of psychoactive substances and their implications for adolescents have been the subject of several studies in Brazil. 9 ),( 10 ),( 11 ) Research on hospitalizations for mental disorders due to the use of psychoactive substances among specific population, encompassing comprehensive nationwide data across the five national macro-regions are scarce. Conducting studies with such age-specific and geographic approaches, along with their characteristics, is important for the development of more integrated and effective mental health policies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20) O declínio das internações na década estudada pode ter sido impulsionado por legislações e estratégias de prevenção e redução de danos da bebida alcoólica e de outras drogas, como a Lei Seca e o programa Crack, é Possível Vencer, (21,22) além de legislações que redefinem o modelo assistencial, com o fechamento dos grandes hospitais psiquiátricos e o redirecionamento para os serviços de atendimento extra-hospitalares, por meio da Rede de Atenção Psicossocial. (23) Essa mudança de cenário corrobora os princípios da Reforma Psiquiátrica, segundo os quais é proposta a consolidação das bases territoriais do cuidado em saúde mental e drogas de abuso. Prevenção, acolhimento e tratamento foram atribuídos a uma rede de cuidados em saúde, a qual inclui a Atenção Primária à Saúde.…”
Section: Modelo R 2 P-value Tendênciaunclassified
“…(22) No entanto, apesar das medidas instituídas pelo governo brasileiro, estudos recentes apontaram que 24,3% dos motoristas brasileiros assumiram a direção do veículo automotor após ter consumido bebida alcoólica, e a violência no trânsito permanece como uma das principais causas de mortes no país, ocupando o segundo lugar de morte por causas externas. (23,26,27) Na análise por regionais de saúde, a única com tendência crescente foi a de Paranaguá. Esse fato pode estar associado à sua localização geográfica no estado, pois se trata de uma cidade portuária, com maior circulação de drogas, diversas formas de acesso e alto consumo de bebida alcoólica por indivíduos que frequentam o porto.…”
Section: Modelo R 2 P-value Tendênciaunclassified